Marketing to the Social Web: How Digital Customer Communities Build Your Business - Larry Weber (John Wiley & Sons, Inc., 2009)
An updated and expanded Second Edition of the popular guide to social media for the business community Marketers must look to the Web for new ways of finding customers and communicating with them, rather than at them. From Facebook and YouTube to blogs and Twitter-ing, social media on the Internet is the most promising new way to reach customers. Marketing to the Social Web, Second Edition helps marketers and their companies understand how to engage customers, build customer communities, and maximize profits in a time of marketing confusion. Author and social media guru Larry Weber describes newly available tools and platforms, and shows you how to apply them to see immediate results and growth. Rather than broadcast messages to audiences, savvy marketers should encourage participation in social networks to which people want to belong, where dialogue with customers, and between customers, can flourish. in Networking sites like MySpace, Facebook, and even Flickr are the perfect forums for this dialog; this book shows you how to tap into this new media. In addition to the tools and tactics that made Marketing to the Social Web a critical hit among marketers, this second edition includes three entirely new chapters that cover recent changes in the field. These new chapters describe how Facebook will monetize its business and one day surpass Google; how companies can measure the influence and effectiveness of their social media campaigns; and how marketing to mobile social media will grow into an effective practice in the near future. Marketing must reach out into new forms, media, and models. Marketing to the Social Web, Second Edition presents an exceptional opportunity to use these new tools and models to reach new markets, even in today's fragmented media environment. Larry Weber has spent the last three decades building global communications companies, including Weber Shandwick Worldwide and the W2 Group. He is also the founder and Chairman of the Massachusetts Innovation and Technology Exchange, the nation's largest interactive advocate association.
Keywords: Business; Internet; Nonfiction; Global Digital Business (BIN2042-N)